2021
DOI: 10.48550/arxiv.2112.10183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust and Privacy-Preserving Collaborative Learning: A Comprehensive Survey

Abstract: With the rapid demand of data and computational resources in deep learning systems, a growing number of algorithms to utilize collaborative machine learning techniques, for example, federated learning, to train a shared deep model across multiple participants. It could effectively take advantage of resource of each participant and obtain a more powerful learning system. However, integrity and privacy threats in such systems have greatly obstructed the applications of collaborative learning. And a large amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
(190 reference statements)
0
1
0
Order By: Relevance
“…SL security is about protecting the integrity of learning process to ensure accuracy and completeness of the trained models. Recent research has shown that malicious participants can influence or even control the model training process in collaborative learning for compromising model integrity [110]. However, how such compromise may be achieved and defended in an SL framework has not been clearly understood thus demanding more thorough study in future research.…”
Section: F Privacy and Security Of Hybrid Sl-flmentioning
confidence: 99%
“…SL security is about protecting the integrity of learning process to ensure accuracy and completeness of the trained models. Recent research has shown that malicious participants can influence or even control the model training process in collaborative learning for compromising model integrity [110]. However, how such compromise may be achieved and defended in an SL framework has not been clearly understood thus demanding more thorough study in future research.…”
Section: F Privacy and Security Of Hybrid Sl-flmentioning
confidence: 99%